'Azerbaijan will turn into the infrastructure hub between Russia and Iran' - Botta, Jorge Paulo (2017)
Early this week (on March 27th and 28th) Iranian President Hassan Rouhani paid an official state visit to Russia. Even though Vladimir Putin and Rouhani met several times in the last three years, those previous visits took place during multilateral meetings so this was the first bilateral visit. The final statement (“Moving towards Comprehensive Strategic Cooperation”) is very clear about the shared regional and global interests of Iran and Russia. Not only about Syria, but also about Yemen, Iraq, Lebanon, Afghanistan, nuclear deal, economic and financial sanctions and global oil and gas markets. During the final press conference both presidents highlighted their determination to expand cooperation and, quite interesting, Rouhani stressed that “the development of our relations is not directed against other countries”. Needless to say that the growing cooperation between those two countries is becoming an important geopolitical development in Eurasia.